The Influence of Domestic Investment, Foreign Investment, and Labor on the Human Development Index (HDI) of Bali Province - Nanda Monika Marpaung; Ni Luh Karmini (Digital Innovation : International Journal of Management, 2025)
The Human Development Index (HDI) is a crucial indicator for measuring the success of human development, encompassing the dimensions of education, health, and a decent standard of living. In Bali Province, disparities in the HDI among regencies/municipalities still exist, which may hinder the overall regional economic development. This study aims to analyze the influence of Domestic Investment, Foreign Investment, and Labor both simultaneously and partially on the Human Development Index during the 2016–2023 period. The data used are secondary data obtained from the Central Statistics Agency, comprising 72 observations. The data collection method employed is the observation method, and the analysis technique used is panel data regression. The results show that (1) Domestic Investment, Foreign Investment, and Labor simultaneously have a significant effect on the Human Development Index of Bali Province, and (2) Domestic Investment partially has no significant effect on the Human Development Index of Bali Province, while Foreign Investment and Labor partially have a positive and significant effect on the Human Development Index of Bali Province.